Genetic diversity and unique genotype identification in togo’s cassava (Manihot esculenta Crantz) germplasm using SNP markers - Gmakouba Tighankoumi; Daniel Kwadjo Dzidzienyo; Koussao Some; Pangirayi Tongoona; Isaac Asante (Cogent Food & Agriculture)
Genetic diversity is a crucial aspect of plant breeding, as it provides the foundation for crop improvement. This study aimed to evaluate the genetic diversity and identify unique genotypes within the cassava germplasm in Togo. To achieve this, 192 cassava accessions from major growing regions were genotyped using 28 genome-wide SNP markers. The results showed that 12 markers were moderately informative, having PIC values between 0.25–0.50, while two markers were less informative, having PIC values below 0.25. The PIC values ranged from 0.11– - 0.37, and major allele frequencies ranged from 0.49–- 0.88. Heterozygosity ranged from 0.09– 0.62, and gene diversity ranged from 0.11–0.50. The germplasm exhibited a moderate genetic diversity level, showing an average expected heterozygosity of 0.42 and observed heterozygosity of 0.50. Hierarchical clustering and PCA identified three distinct genotypic groups. Additionally, 60 duplicate accessions were detected based on SNP profiles. AMOVA analysis indicated that the observed genetic diversity was primarily due to differences between accessions. The core cassava set developed in this study will serve as an invaluable resource for future genomic research and strategies for the improvement of the crop.